A Novel Method for the Treatment of Bilateral Hypogastric Aneurysms Using Hybrid Polytetrafluoroethylene Graft. (May 2017) - Tyagi, Sam; Pineda, D.; Zheng, H.; Dougherty, M.; Calligaro, K.; Troutman, D.
Open aortic aneurysm repair in the setting of bilateral hypogastric aneurysms is technically challenging. We present a novel technique for open surgical repair for bilateral hypogastric aneurysms using the Gore hybrid vascular graft (GVHG; W. L. Gore and Associates Inc, Flagstaff, Arizona). The GVHG is an expanded polytetrafluoroethylene graft with a nitinol stent at 1 end designed for hemodialysis access. The GVHG has been also been used for aortic debranching and treatment of occlusive disease. We describe the first report using GVHG to repair hypogastric aneurysms.